Formulation, Development and Evaluation of Ciclopirox Olamine Nanogel for the Treatment of Cutaneous Candidiasis - Kotsulwar, Nivrutti A.; N. Nagoba, Shivappa; B. Malshette, Rachita; G. Girwalkar, Gaurav; R. Alande, Anjali (Journal of Neonatal Surgery, 2025)
Background: Cutaneous candidiasis is a superficial fungal infection predominantly caused by Candida albicans, often affecting moist skin areas. To overcome limitations of conventional topical antifungal treatments, such as poor skin penetration and frequent application, this study aimed to formulate, develop, and evaluate a nanogel containing Ciclopirox Olamine for improved topical delivery. Methods: Nanogels (F1–F4) were prepared using the emulsion-solvent diffusion method, incorporating Carbopol 934 as gelling agent, PEG-600 and propylene glycol as co-solvents, Tween 80 as surfactant, and triethanolamine as a pH adjuster. Results: All formulations were evaluated for physicochemical properties. F4 demonstrated optimal performance: pH 5.67, spreadability 6.9 g·cm/s, viscosity 22200 cps, drug content 92.93%, and entrapment efficiency 92.1%. The drug and excipient compatibility was verified by FTIR.. UV analysis showed a λmax at 256 nm with linearity between 2–8 µg/mL. SEM revealed spherical particles; DLS showed Z-average particle size of 115.8 nm with PDI 0.828; zeta potential was -19.7 mV, indicating moderate stability. In vitro drug diffusion studies showed maximum drug release for F4 at 93.68% over 8 hours. Antifungal efficacy via well diffusion showed a 17 mm zone of inhibition for F4 against Candida albicans, compared to 24 mm for the standard (Miconazole). MIC was determined at 31.2 µg/mL, and MFC analysis confirmed effective fungal eradication at higher concentrations. Conclusion: The optimized nanogel (F4) thus offers improved penetration, sustained release, effective antifungal action, and better patient compliance, making it a promising candidate for the topical treatment of cutaneous candidiasis.